PENGARUH UKURAN PERUSAHAAN, LAVERAGE, DEWAN KOMISARIS INDEPENDEN, KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN MANEJERIAL TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2011-2014) - Veronica M; Kirmizi Kirmizi; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to analyze and gets empirical prove of size of company, leverage, board of commissioners independen, institutional ownership and managerial ownership on earnings management. The population in this research were manufacturing sector companies listed on the Indonesian Stock Exchange (IDX) year period from 2011 to 2014. Purposive sampling method is used to determine the sample, while the data processing methods used are multiple regression analysis by using SPSS version 19.0 as the software for processing data. With the sampling method, it is found samples as many as 152 companies that were used in this study. The results prove that size of company, leverage has no signicant effect on earnings management, this is indicated from its significance value more than 0.05. While board of commissioners independen, institutional ownership, managerial ownership has a significant effect on earnings management significantly by 0.005.Keywords : Eearnings Management, Size of Company, Leverage, and Good Corporate Governance